Beyond the Sharia State: Public Celebrations and Everyday State-Making in the Malay Islamic Monarchy of Brunei Darussalam - Müller, Dominik (Asian Journal of Law and Society, 2022)
This article describes post-colonial state-making in the absolute monarchy of Brunei. After detailing the Sultan’s powers, contextualizing the monarchy’s stability, and introducing its state ideology, Melayu Islam Beraja (“MIB”), the article addresses formal laws, such as Brunei’s Constitution and a new Islamic penal code, which are symbolically significant for the MIB state’s (self-)legitimation but have little immediate relevance to many Bruneians’ lives. The article, therefore, shifts its focus to normative spheres that receive much less scholarly attention but, arguably, should—namely state-rituals like the Sultan’s three-week-long birthday celebrations. These, and other non-legal spheres, including, also, royal speeches, contain normative aspects that reflect and impact key developments in the MIB state. Grounded in the Royal Birthday’s and Islamic penal code’s analysis, the final part problematizes stereotypes of Brunei being a “sharia state” vis-à-vis its multidirectional normative messages and ability to hybridize broad cultural influences for the ruling system’s benefit.<br
Keywords: Brunei Darussalam; absolute monarchy; everyday state-making; Royal Birthday; Islamic law